Restoration of p53 expression sensitizes human papillomavirus type 16 immortalized human keratinocytes to CD95-mediated apoptosis - Carmen Aguilar Lemarroy, Adriana del; Zur Hausen, Harald; Krammer, Peter H.; Rösl, Frank (Oncogene, 2002)
To understand the function of the individual oncogenes of HPV16 in modulating the cellular response to apoptogenic signals, we used human keratinocytes immortalized with either E6, E7 or E6/E7 oncoproteins as model system. Applying CD95 antibodies or recombinant CD95 ligand, only the E7-immortalized cells underwent extensive apoptosis. In contrast, E6- and E6/E7-expressing keratinocytes were resistant. Dominance of E6 correlated with significant down-regulation of p53, c-Myc, p21 and Bcl-2. CD95 was found to be reduced in resistant HPV-positive cells, while there were no quantitative differences in expression levels of FADD, FLICE/caspase-8 or caspase-3. Notably, in contrast to primary human keratinocytes, all immortalized cells showed a general reduction of c-FLIP, an inhibitory protein which normally prevents unscheduled CD95-induced apoptosis. E6- and E6/E7-positive keratinocytes, however, can be sensitized to CD95 apoptosis by blocking proteasome-mediated proteolysis. CD95-resistant HPV-positive cells underwent apoptosis within 3-5 h upon co-incubation with MG132 and agonistic antibodies or CD95 ligand, which was preceded by a strong re-expression of p53 and c-Myc, but not of other half-life controlled proteins such as Bax or IκBα. Blockage of proteasomal activity alone did not result in apoptosis, although the same set of pro-apoptotic proteins was up-regulated. Performing similar experiments with cervical carcinoma cells expressing mutated p53 (C33a) or with p53-‘null’ lung carcinoma cells (H1299), no CD95 cell killing occurred eventhough c-Myc was strong induced. These data indicate that the reduced bioavailability of p53 is a key-regulatory event in perturbation of CD95 signaling in HPV16 immortalized keratinocytes.
Gesehen am 20.04.2021